LAY UNDERSTANDING OF LEGAL TERMINOLOGY IN THE ERA OF THE JAPANESE LAY JUDGE SYSTEM - OKAWARA, Mami Hiraike (Comparative Legilinguistics, 2012)
This paper discusses the unintelligible nature of legal terminology from lay perspectives in the era of the lay judge system. First, I will introduce Japan’s first plain language project which was set up by the lay-judge preparatory headquarters of Japan Federation of Bar Associations in preparation in 2005 for the lay judge system introduced in 2009. The project paraphrased sixty-one legal terms, which were important for lay judges but not known to lay people. I will show some rewording work, which was conducted by joint effort between legal and non-legal experts of the project. After the discussion of the rewording work I will move to a mock lay judge trial which was held by Maebashi District Courts, together with Maebashi District Public Prosecutors’ Offices and Gunma Bar Association in 2006 to prepare for the lay judge system. I will focus on one unintelligible legal terminology, ‘murder through willful negligence’ (mihitus no koi) and discuss how the intent to murder was determined in a deliberation of a mock trial, using a discourse connective, ‘the only thing is that…’ (tada). The introduction of the lay judge system has therefore given a prodigious opportunity to work on plain legal language in Japan.